2019
DOI: 10.3390/molecules24050910
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Homoleptic Copper Complexes of Curcuminoids: Synthesis, Characterization and Biological Properties

Abstract: We report herein the synthesis and crystal structures of five new homoleptic copper complexes of curcuminoids. The scarcity of reports of homoleptic complex structures of curcuminoids is attributed to the lack of crystallinity of such derivatives, and therefore, their characterization by single crystal X-ray diffraction is rare. The ligand design suppressing the phenolic interaction by esterification or etherification has afforded a significant increase in the number of known crystal structures of homoleptic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The four homoleptic complexes studied inhibited lipid peroxidation in the rat brain tissue model with higher activity than α-tocopherol and comparable to BHT. It is noteworthy that all copper complexes synthesized in our previous report [21] as well as the copper complex in the present one, exhibited considerable antioxidant effect but negligible cytotoxicity. Of special significance is the remarkable cytotoxic effect found for (DAC) 2 Mg and (DAC) 2 Zn against HCT-15, MCF-7 and SKLU-1 human cancer cell lines, which surprisingly equated or surpassed that of cisplatin.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The four homoleptic complexes studied inhibited lipid peroxidation in the rat brain tissue model with higher activity than α-tocopherol and comparable to BHT. It is noteworthy that all copper complexes synthesized in our previous report [21] as well as the copper complex in the present one, exhibited considerable antioxidant effect but negligible cytotoxicity. Of special significance is the remarkable cytotoxic effect found for (DAC) 2 Mg and (DAC) 2 Zn against HCT-15, MCF-7 and SKLU-1 human cancer cell lines, which surprisingly equated or surpassed that of cisplatin.…”
Section: Discussionsupporting
confidence: 57%
“…The copper and manganese complexes of diacetylcurcumin have been reported previously [8,16], however, the X-ray structures have not been reported. In a recent work by Meza-Morales et al (2019), the synthesis of five homoleptic complexes, with copper was reported using different curcuminoids [21], along with their single crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining single crystals of mixed chelate copper(II) coordination compounds with curcuminoids as ligands is complicated due to the low solubility of the complexes, with few reports in the literature [ 39 , 66 , 67 ]. Small crystals of the analogous complexes D5CuL2 and D6CuL2 were obtained ( Figure 9 and Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of Compounds 1–4. Chemical reactions were conducted under mild experimental conditions similar to those previously reported [ 44 , 45 , 46 ]. Thus, in a 250 mL round-bottom flask, 1 g of curcumin was dissolved in dry acetone and an excess of anhydrous potassium carbonate (6 Eq, 1.12 g) and benzyl bromide (6 Eq, 1.9 mL) pre-dissolved in acetone were added dropwise to the curcumin solution under stirring.…”
Section: Methodsmentioning
confidence: 99%